Strategic Management in Tourism Industry: A Perspective Article during Pandemic - Evanthi , Ayundha; Azhar, Ratih Mukti (Nusantara Science and Technology Proceedings, 2023)
The purpose of this essay is to critically evaluate recent research on strategic management (SM) in pandemic situations and to suggest potential future possibilities for SM research in the hospitality and tourist (HT) sector. The current state of SM research in the HT field was examined critically in this study, along with potential future prospects. SM research with an HT focus still has a weak social structure. The field's scientific development has slowed down because there aren't many top researchers in it. Finally, researchers in the HT field should publish their findings in prestigious academic publications that cover both the HT and mainstream fields. This study uses VOSviewer to display how bibliometric analysis of multiple older articles was used to define strategic management in the hospitality and tourist industry. The results indicate that strategic management research in the hospitality and tourist sectors has advanced during the course of the study; nonetheless, there is still a gap between the two sectors' strategic management research.